Characteristics and Advantages of Sea Transportation - Monica Amanda; Yunita Panggabean; Muhammad Taufiqurrahman; Oktarina Hidayati (IWJ : Inland Waterways Journal, 2020)
Indonesia is an archipelago whose land area is separated by a very large area of water, so the role of sea transportation is very important in connecting all regions in Indonesia. The function of sea transportation is basically to transport passengers or goods from one place to another which is separated by water areas. With the existence of sea transportation, it can help create a national distribution pattern. However, to achieve this, an effective, efficient and safe marine transportation system is needed. The movement or movement of passengers and goods is the basis for trade. Through sea transportation, raw materials and goods produced from one area can be marketed to other regions. Indonesia,Shipping in inland waters is one of the oldest transportation for people and/or goods which is economical and environmentally sound and for inland areas it may be the only mode of transportation for access to markets and other social activities. The modes of transportation can range from bamboo rafts to motorized boats that can operate in small rivers, lakes to large rivers.In this case using qualitative descriptive method. Descriptive research is the basis of all research. Data collection was done by using literature study method. Search for literature that supports research both from books and journals related to the research topic being carried out.